Variation of gene ratios in mock communities constructed with purified 16S rRNA during processing - Georges Mikhael Nammoura Neto; René Peter Schneider (Scientific Reports)
Abstract 16S ribosomal nucleic acid (16S rRNA) analysis allows to specifically target the metabolically active members of microbial communities. The stability of the ratios between target genes in the workflow, which is essential for the bioprocess-relevance of the data derived from this analysis, was investigated using synthetic mock communities constructed by mixing purified 16S rRNA from Bacillus subtilis (Bs), Staphylococcus aureus (Sa), Pseudomonas aeruginosa (Pa), Klebsiella pneumoniae (Kp) and Burkholderia cepacia (Bc) in different proportions. The RT reaction yielded one copy of cDNA per rRNA molecule for Pa, Bc and Sa but only 2/3 of the expected cDNA from 16S rRNAs of Bs and Kp. The combination of Taq DNA Platinum polymerase with subcycling PCR (scPCR) produced uniform yields of approximately 70% for second strand PCR synthesis from all target cDNAs. The proportion between templates in multicycle PCR was best preserved after 10 cycle scPCR followed by cloning. With MiSeq sequencing, correct proportions for about two thirds of templates were recovered after 10 cycle scPCR with Taq Platinum. 30 cycles standard PCR (stdPCR) or scPCR proved particularly harmful to proportion data and should be avoided.